Why more male pedestrians die in vehicle-pedestrian collisions than females: a decompositional analysis - Zhu, Motao (2012)
OBJECTIVE: Pedestrians account for a third of the 1.2 million traffic fatalities annually worldwide, and males are overrepresented. We examined the factors that contribute to this male-female discrepancy: walking exposure (kilometers walked per person-year), vehicle-pedestrian collision risk (number of collisions per kilometers walked), and vehicle-pedestrian collision case fatality rate (number of deaths per collision). DESIGN: The decomposition method quantifies the relative contributions of individual factors to death rate ratios among groups. The male-female ratio of pedestrian death rates can be expressed as the product of three component ratios: walking exposure, collision risk, and case fatality rate. Data sources included the 2008–2009 U.S. Fatality Analysis Reporting System, General Estimates System, National Household Travel Survey, and population estimates. SETTING: U.S. PARTICIPANTS: Pedestrians age 5 and older. MAIN OUTCOME MEASURES: death rate per person-year, kilometers walked per person-year, collisions per kilometers walked, and deaths per collision by sex. RESULTS: The pedestrian death rate per person-year for males was 2.3 times that for females. This ratio of male to female rates can be expressed as the product of three component ratios: 0.995 for walking exposure, 1.191 for collision risk, and 1.976 for case fatality rate. The relative contributions of these components were 1%, 20% and 79%, respectively. CONCLUSIONS: The majority of the male-female discrepancy in 2008–2009 pedestrian deaths in the U.S. is attributed to a higher fatality per collision rate among male pedestrians.